ANALISIS PENGARUH KOMPENSASI DAN KOMUNIKASI ORGANISASI SERTA KOMITMEN ORGANISASI TERHADAP BUDAYA ORGANISASI DAN KINERJA ORGANISASI PT. BANK RAKYAT INDONESIA (PERSERO) TBK SURABAYA TANJUNG PERAK - wahyudi, wahyudi; supriyanto, joko (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRAKThe purpose of this study is to see the effect of organizational communication commitment compensation commitment to work culture and Performance of BRI partially and simultaneously at BRI Surabaya branch office Tanjung Perak. This study uses data in the form of questionnaires given to 106 respondents, who are employees of BRI using SEM analysis. The results of hypothesis research and testing show that (1) there is no influence between compensation to organizational culture; (2) There is influence between organizational communication to organizational culture; (3) There is an influence between organizational commitment to organizational culture; (4) There is no influence between compensation on the performance of BRI; (5) There is an influence between organizational communication on the performance of BRI; (6) There is no influence between organizational commitment to BRI's performance; (7) There is an influence between organizational culture on the performance of BRI.Â Keywords: Compensation, Organizational Communication, Organizational Commitment, Organizational Culture and Organizational Performanc